Clozapine versus other antipsychotics during the first 18 weeks of treatment: A retrospective study on risk factor increase of blood dyscrasias. (October 2017) - Fabrazzo, Michele; Prisco, Vincenzo; Sampogna, Gaia; Perris, Francesco; Catapano, Francesco; Monteleone, Alessio Maria; Maj, Mario
Abstract: Blood dyscrasias excluding agranulocytosis received limited attention in antipsychotic-treated patients during the first 18 weeks of therapy, although severe clinical conditions have been reported in a few cases. We extracted data records of 285 Caucasian patients after 18 weeks of antipsychotic treatments to investigate risk factors of blood dyscrasias. We observed a higher risk to develop both transient and persistent anemia, neutrophilia and eosinophilia in clozapine-treated patients, whereas in those treated with other atypical antipsychotics when compared to a reference group under typical antipsychotics, emerged an increased risk for transient neutrophilia and eosinophilia. Male patients revealed a higher risk of persistent eosinophilia, neutrophilia, and leukocytosis. Concomitant treatments with mood stabilizers or benzodiazepines proved to be risk factors for transient anemia, antidepressants for transient eosinophilia. Severe complications emerged in 3 cases of agranulocytosis. Cross-tabulation analysis showed a higher probability of a poor response in clozapine-treated patients with persistent anemia and a positive with persistent neutrophilia and eosinophilia. Our data evidenced that emerging blood dyscrasias were not associated with critical adverse effects, and only agranulocytosis required a treatment interruption. Other atypical antipsychotics might represent a viable alternative to potentially harmful clozapine and typical antipsychotics at the onset of life-threatening haematological alterations. Highlights: Blood dyscrasias arose in most clozapine and other antipsychotic-treated patients. Male patients were at major risk for leukocytosis, neutrophilia and eosinophilia. Mood stabilizers and benzodiazepines increased the risk for transient anemia only. A positive clinical response to clozapine was most associated with neutrophilia and eosinophilia. Atypical antipsychotics appeared valid alternatives to clozapine when risks emerged.